(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The increasingly complex nature of the global business environment demands a more comprehensive approach to investment decision-making and project valuation. Traditional approaches, which focus on financial aspects, are considered insufficient to fully account for the dynamics of modern investment, which involve various dimensions of value. This study aims to identify and synthesise theoretical developments and the factors influencing investment decisions and project value based on the latest scientific literature. This study employs a Systematic Literature Review (SLR) approach following the PRISMA protocol. Data were collected from the Scopus, Google Scholar, and SSRN databases covering the publication period 2021–2025. Data analysis was conducted through the stages of screening, coding, and thematic synthesis to identify patterns, approaches, and key findings in previous research. The findings indicate a shift towards the integration of non-financial factors, particularly ESG, the use of more adaptive evaluation methods such as real options, and the application of artificial intelligence in investment analysis. Furthermore, behavioural factors and corporate governance have been shown to play a significant role in enhancing the quality of investment decisions. This study underscores the importance of a multidimensional approach to investment evaluation for practitioners and policymakers.